THE USE OF MOBILE CELLULAR PHONES IN MICROENTERPRISES - Tsotetsi, Khopotso (My University, 2011)
This report presents the findings of an applied research study designed to explore the use of mobile cellular phones in micro-enterprises based at Pretoria. In particular, the report, considers the core research question: Are informal, survivalist micro-enterprises based in Pretoria realising the full potential of cellular phones to support the growth, development and sustainability of their businesses? What measures must be taken to advance the effective use of mobile cellular phones in informal, survivalist micro-enterprises. The context of the study is the assertion expressed in literature that indicates that the survival changes of micro-enterprises in South Africa beyond a period of three years is poor, despite the potential of mobile cellular phones to support productivity and efficiency gains in business. Hence, the exploratory study was designed to contribute towards the formulation of appropriate polices, strategies and interventions to improve micro-enterprises’ use of mobile cellular phones as tools to support business development. The study is also informed by the stipulations of the United Nations World Summit on Information Society Declaration which was signed by a significant number of heads of state in 2003. The WSIS Declaration (2003) indicates that that information and communication technologies (ICTs) are an important enabler of small enterprises’ growth through efficiency gains and increased productivity. Moreover, productivity growth depends on using existing tools more effectively and efficiently to yield bigger results. A focus group methodology was employed to enable the realisation of the research aim and question. The methodology allowed for a detailed explanation on experiences, perceptions, and why particular use patterns of cellular phones are prevalent amongst informal, survivalist micro-enterprises. The methodology also enabled the participants to put the experiences in their own words, and express attitudes, feelings, experiences, meaning and rationale underpinning usage. Moreover, the report also outlined a wide range of relevant literature and research studies that shed light on the topic. The study did not seek to draw conclusions for generalisation, rather, it has endeavoured to encourage reflection, deepen existing research and inform further debate. ii The report revealed that in order to understand usage of mobile services, as a precursor, it is important to understand the micro-enterprise business needs, in terms of the form of business they own, characteristics thereof, their information needs and information sourcing practices. The study affirmed that a mobile cellular phone is an integral part of micro-enterprises, consistent with key arguments of numerous researchers and authors. Two statements of some of the focus group members capture the essence of the sentiments expressed about the significance of a mobile cellular phone in micro-enterprises, namely, “If I can stop to use a cell phone, my business would suffocate and die”. ”A cell phone for me is my office”. The report revealed that the micro-enterprises in Pretoria used the mobile cellular phone to communicate and interact with other businesses and customers. However, the micro-enterprise owners did not use a cellular phone effectively to attain support from Government and transact with public entities. It also emerged from the study that the most used functions or services of a cellular phone in micro-enterprises were a voice call and short text messages. A mobile TV, internet, video and camera functions were not widely and effectively utilised in the businesses. The report concludes that though the microenterprise owners from Pretoria which participated in the focus group had an access to mobile cellular phones, they did not fully utilise all the features, applications and services available to support business activities. A cellular phone had a potential to support micro-enterprise growth and development but the potential thereof was not fully realised in the micro-enterprises. It was also revealed that the model of a cellular phone, form of business activities engaged by the microenterprise, needs of the business, level of awareness and socio-economic factors such as age, skills of the owner and the cost of the technology influenced the mobile cellular phone usage pattern of micro-enterprise owners that participated in the focus group. The main recommendation of the report is that Government should package information and services to convey over the cellular phone for micro-enterprises to use and should intensify awareness programmes to educate the micro-enterprise owners about how the cellular phone applications can be used effectively in business
MM - P&DM
Keywords: Micro enterprises; Mobile telecommunications; Cell phones